Vanadyl tetrabutyltetrakis(Dimethylamino) phthalocyanine based thin films for organic sensor and transistor applications / Nur Adilah Roslan - Nur Adilah , Roslan (2020)
Organic electronic devices have been successively making progress into the commercial market to substitute conventional inorganic electronic devices. The endeavor to improve the performance displayed by organic semiconductor materials has urged a substantial number of researchers set to seek new materials. Metal phthalocyanines (MPcs), in particular, have garnered much attention due to their enticing benefits viz., cost efficiency, eco-friendly organic material, as well as thermal and chemical stability. Primarily, this study investigated the physical, morphological, optical, and electrical properties of vanadyl 3,10,17,24-tetra-tert-butyl-1,8,15,22-tetrakis(dimethylamino)-29H,31H-phthalocyanine or synonymously known as vanadyl tetrabutyltetrakis (dimethylamino) phthalocyanine (VTP). Subsequently, this study looked into the potential applications of VTP-based organic semiconductor devices in organic field effect transistor (OFET), as well as optical and humidity sensor. The initial phase of this study is devoted to the characterization of VTP thin films and fabrication of VTP-based OFETs. The photophysical study revealed that the band gap of VTP is 1.39 eV via expression approach, while 1.42 eV via Tauc plot. The highest occupied/lowest unoccupied molecular orbital (HOMO/LUMO) values of VTP were -5.10 eV and -3.90 eV, respectively, as determined via cyclic voltammetry (CV) analysis. The VTP was applied as the active layer in the fabrication of lateral OFETs (LOFETs), which served as a control device, whereby fixed parameters were employed for each layer, similar for the fabrication of vertical OFETs (VOFETs). The LOFETs exhibited poor performance due to the extended channel length between source and drain (S-D) electrodes. In the attempt of addressing this shortcoming, apart from enhancing the performance of LOFETs; the arrangement was altered to resemble that of VOFET, in which capacitor and diode cells were vertically stacked on top of each other. This design minimized the channel length and enhanced the device performance. In attaining optimum thickness for the active layer, VOFET was fabricated with a range of thicknesses; 90  5 nm, 66  5 nm, and 52  5 nm. As a result, VTP thickness at 66  5 nm exerted optimum performance, as it generated maximum current density and the lowest threshold voltage of ~ 37 mA/cm2 and 7.0  0.2 V, respectively. The second phase of this study probed into the fabrication of VTP-based optical organic devices. Initially, the study of optical properties and charge transport via current-voltage (I-V) method was executed. Utilizing the optimized bulk heterojunction (BHJ), ITO/PEDOT:PSS/VTP:PC71BM/Al organic photovoltaics (OPVs) were fabricated by using the solution processed technique. By employing the similar OPV fabrication parameters, the device was used for light sensing application, which falls under the organic optical device category. The light sensor appeared to display high stability, rapid response time, and high sensitivity in the visible light. These features are attributable to the extended ligands in the molecular structure of VTP. The final phase of this study assessed the applicability of VTP as an active layer in the fabrication of organic humidity sensor. Physical characterization that involved structural and wettability evaluations were executed in advance to determine the association between the thickness of sensing film and the performance exerted by the sensor. The Al/VTP/Al humidity sensor devices were fabricated in three thickness values, which revealed that the thinnest sensing film displayed the best performance with a maximum sensitivity of 9.2 pf/%RH. In sum, this study had successfully adopted highly reproducible, solution generating, and cost-efficient fabrication techniques.